PENGARUH KEPEMILIKAN MANAJERIAL, KARAKTERISTIK KOMITE AUDIT, UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP KECURANGAN PELAPORAN KEUANGAN PADA PERUSAHAAN NON KEUANGAN DI BURSA EFEK INDONESIA - Melanthon Rumapea; Duma Megaria Elisabeth; Diana Monica (METHOSIKA: Jurnal Akuntansi dan Keuangan Methodist, 2022)
This study aims to determine the Effect of Managerial Ownership, Characteristics of the Audit Committee, Company Size, and Leverage on Financial Reporting Fraud in non-financial companies on the Indonesia Stock Exchange. The sample selection used purposive sampling with a sample size of 42 from 67 non-financial companies on the Indonesia Stock Exchange. The independent variables studied were Managerial Ownership, Characteristics of the Audit Committee, Company Size, and Leverage while the dependent was Financial Reporting Fraud. The results of this study indicate that Managerial Ownership, Characteristics of the Audit Committee (Independence of the audit committee), and Company Size has no significant effect on Fraudulent Financial Reporting. Characteristics of the Audit Committee (audit committee's financial expertise), Leverage has a significant effect on Financial Reporting Fraud.